Global dynamics of a delay virus model with recruitment and saturation effects of immune responses - Cuicui Jiang; Kaifa Wang; Lijuan Song (Mathematical Biosciences and Engineering)
In this paper, we formulate a virus dynamics model with the recruitment of immune responses, saturation effects and an intracellular time delay. With the help of uniform persistence theory and Lyapunov method, we show that the global stability of the model is totally determined by the basic reproductive number $R_0$. Furthermore, we analyze the effects of the recruitment of immune responses on virus infection by numerical simulation. The results show ignoring the recruitment of immune responses will result in overestimation of the basic reproductive number and the severity of viral infection.